1993
DOI: 10.1590/s0004-282x1993000400001
|View full text |Cite
|
Sign up to set email alerts
|

The role of sleep in migraine attacks

Abstract: Migraine attacks may be precipitated by sleep deprivation or excessive sleep and sleep is also associated with relief of migraine attacks. In view of this variable relationship we studied the records of 159 consecutive outpatients of our Headache Unit. In 121 records there was reference to sleep involvement, in 55% by a single form and in 45% by more than one form. When only one form was related, relief was most common (70%). 30% of that group of patients had the migraine attack precipitated by sleep, 24% by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 15 publications
0
28
0
2
Order By: Relevance
“…[21][22][23][24][25][26] Previous studies have also linked sleep deprivation to headaches. 27,28 Most of the medical residents undergo self-medication and only a few consult physicians for headache. Some previous studies also show similar facts.…”
Section: -12mentioning
confidence: 99%
“…[21][22][23][24][25][26] Previous studies have also linked sleep deprivation to headaches. 27,28 Most of the medical residents undergo self-medication and only a few consult physicians for headache. Some previous studies also show similar facts.…”
Section: -12mentioning
confidence: 99%
“…16 There is a paradoxical relationship, in which sleep deprivation or excess can lead to worsening headaches, but sleep onset can relieve an ongoing migraine. 17 There are a number of shared anatomical sites in the brainstem and the hypothalamus that are active in migraine and sleep. 18,19 A number of studies have looked at the relationship between sleep and headache.…”
Section: Relationship Between Sleep and Headachementioning
confidence: 99%
“…[94][95][96] Yet, the treatment of the sleep disorder alleviates both morning headache and migraine. 97 Futhermore, alpha EEG sleep, as well as sleep related breathing disorders and periodic limb movement disorders, happen in some patients with FMS, rheumatoid arthritis and osteoarthritis. 87 Also, patients with irritable bowel disorder commonly complain of disturbed sleep and studies have shown that they have increased REM sleep.…”
Section: Sleepmentioning
confidence: 99%